Application of CRISPR/Cas9 System in Establishing Large Animal Models - Lin, Yingqi; Li, Jun; Li, Caijuan; Tu, Zhuchi; Li, Shihua; Li, Xiao-Jiang; Yan, Sen (Frontiers in Cell and Developmental Biology, 2022)
The foundation for investigating the mechanisms of human diseases is the establishment of animal models, which are also widely used in agricultural industry, pharmaceutical applications, and clinical research. However, small animals such as rodents, which have been extensively used to create disease models, do not often fully mimic the key pathological changes and/or important symptoms of human disease. As a result, there is an emerging need to establish suitable large animal models that can recapitulate important phenotypes of human diseases for investigating pathogenesis and developing effective therapeutics. However, traditional genetic modification technologies used in establishing small animal models are difficultly applied for generating large animal models of human diseases. This difficulty has been overcome to a great extent by the recent development of gene editing technology, especially the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9). In this review, we focus on the applications of CRISPR/Cas9 system to establishment of large animal models, including nonhuman primates, pigs, sheep, goats and dogs, for investigating disease pathogenesis and treatment. We also discuss the limitations of large animal models and possible solutions according to our current knowledge. Finally, we sum up the applications of the novel genome editing tool Base Editors (BEs) and its great potential for gene editing in large animals.